Development of weld repair methods for Rene 80 nickel based superalloy - Rush, Matthew T. (Cranfield University, 2012)
Nickel based superalloys are an integral material for gas turbines, where their excellent high temperature mechanical properties and corrosion resistance are utilised. Due to the increasing costs of raw materials, manufacturers are interested in repairing in-service and manufacturing defects in components. Unfortunately, superalloys such as Rene 80 are highly susceptible to welding defects such as liquation cracking and post-weld heat treatment cracking, which make repair welding highly difficult. The aim of the research in this thesis was to develop an improved understanding of welding defect production in nickel-based superalloys. In particular, the effect of repair process and its parameters were examined, with the ultimate aim to produce crack-free repair welds. The main theme of the work involved a large parametric study of the process parameter effects on welding defects in Rene 80 using a high power fibre laser. This work determined an optimised range of parameters which reduced the incidence of cracking. Furthermore, this work also identified a key relationship between the weld bead geometry aspect ratio and the incidence of cracking. This relationship was studied using neutron diffraction to determine the differences in strain and residual stresses between two welds with identical heat input but different geometry. An in-depth investigation of the cracks within the material, identified that as-welded cracks formed via liquation of secondary phases such as carbides, γ/γ’ eutectics, and secondary gamma prime. The post weld heat treatment cracks formed by the strain-age mechanism in Rene 80. From this work, a novel repair procedure avoiding the complications associated with using lower strength filler metal was developed, based on the optimised welding parameters. Finally, a number of advanced low heat input welding processes were also investigated for repair of superalloys.